Producción de ácido láctico a partir de la fermentación de biomasa celulósica del afrecho de malta mediante bacterias lácticas (2024)
Lactic acid has multiple applications in the food, pharmaceutical, textile industries and lately, in the production of bioplastics; Due to its importance and wide demand, a strategy for using malt bran for the laboratory-scale production of lactic acid by fermentation using a bacterial consortium between the lactic acid bacteria Lactobacillus delbrueckii and Streptococcus thermophilus is presented.